Impact of gastrointestinal hemorrhage on hospital outcomes of patients with hypertrophic cardiomyopathy. (14th October 2021) - Shah, K; Thyagaturu, H; Mughal, M; Gandhi, H; Harmouch, F; Modi, V; Kothari, J; Shirani, J
Abstract: Background: Patients with hypertrophic cardiomyopathy (HCM) may be at relatively high risk of gastrointestinal hemorrhage (GIH) due to acquired von Willebrand disease (aVWD) and anticoagulation for atrial fibrillation among others factors. Purpose: We aimed to evaluate impact of GIH on in-hospital outcomes of patients with HCM. Methods: The National Inpatient Sample reported 45, 305 admissions for adults with HCM during a two-year period (2016–2017). Among them, 1, 490 patients (3.3%) also had GIH. Baseline characteristics and in-hospital outcomes of the two groups were compared. Multivariable logistic regression analysis was used to assess the independent impact of GIH on in-hospital outcomes of HCM patients. Results: Out of 45, 305 HCM patients, 1490 (3.2%) also had concomitant diagnosis of GIH. HCM patients with GIH were older (70±9 vs 66±23 years), were more often male (64% vs 61%), and had higher prevalence of prior myocardial infarction (12% vs 7%, p<0.001) and cirrhosis (7.1% vs 2.6%, p<0.001) while being less often obese (15% vs 22%, p=0.01) or having a history of congestive heart failure (30% vs 36%, p=0.03) [Table 1]. Hospital mortality was significantly higher among those with GIH (6.4% vs 3.5%, p<0.001). Multivariable logistic regression analysis identified GIH as an independent predictor of higher in-hospital mortality [adjusted odds ratio (aOR)=1.60, 95% confidence interval (CI)=1.02–2.63, p=0.001], hypovolemic shock (aOR=5.17, 95% CI=2.5–10.6, p<0.001), mean length of stay (Δ +2.4 days, p<0.001) and mean hospital cost (Δ +$21, 162, p=0.004). Conclusion: Adults with HCM and GIH are older, less often obese with higher prevalence of cirrhosis and prior myocardial infarction. Presence of GIH is an independent predictor of higher mortality, hypovolemic shock, length of stay and hospital cost in HCM adults admitted to hospital. Funding Acknowledgement: Type of funding sources: None.